Nematode/copepod ratio and nematode and copepod abundances as bioindicators of pollution: a meta-analysis - Michel Sciberras; Agustín G. Menechella; Kevin A. Rucci; Néstor J. Cazzaniga; Hugo J. Marrero (Ecología Austral, 2022)
Meiofauna has been considered a suitable group for monitoring pollution effects. Based on different pollution tolerance, a nematode/copepod ratio was proposed as an easy tool for monitoring the effect of anthropogenic activities. Although the validity of this tool has been subject to debate due to controversial results, it is still widely used. To establish a general pattern in the response of the ratio and nematode and copepod abundances to the effects of organic enrichment, oil pollution and metal enrichment in the marine environment, we conducted a global-scale meta-analysis. The database consisted of 715 pairs of data obtained from 46 studies published during the last 39 years. We could not find a general trend in the response of nematode and copepod abundances to these pollutants. Regarding the ratio, the only significant difference we found is under the effect of oil pollution. However, this difference appears to be an artifact due to publication bias. The information gathered in this study suggests that the ratio and mean abundances are not reliable tools for monitoring purposes.